QUALITY TOOLS AND THEIR APPLICATIONS IN TROUBESHOOTING: case study in an automotive company - Vitorio, Rafael Aparecido Ferreira; Antônio, Fabrício Domingues (Revista Interface Tecnológica, 2020)
During the production processes of a company, we face problems related to the process, equipment and unskilled employees on a daily basis. These unforeseen events prevent the production schedule, or even interfere with the quality of the final product and, consequently, with the credibility of your customer. Meeting customer satisfaction is what companies seek, that´s why the quality management system has to ensure that the final product is the result of the production process. Any and all non-conformities found in the process will be presented in the final product, but for that not to happen there are some tools that can be used in the process. This paper aims to show the importance of these tools in a production process and how to use them in a way that brings benefits to the organization, by eliminating wastes, having efficiency and gains in productivity and support in guaranteeing the final product. Through a case study in an automotive company, it was presented the use of quality tools to solve the problem, bringing a positive result so that the failure does not occur anymore, serving as a model for other production items. This work was developed based on bibliographic searches through books and papers as well as a case study in an automotive company.